EFEKTIVITAS DAN LAJU PERTUMBUHAN PAJAK BUMI DAN BANGUNAN DI ACEH BARAT - Mahrizal Mahrizal (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2018)
Giving autonomy to the regions is one of the important elements of reform. Autonomy provided by the central government in the Regency or City is expected to be an area that is developed and independent. Land and Building Tax (PBB) is one of the central government revenues, with a portion of the proceeds (around 80 percent) handed over to the regions concerned. Land and Building Tax (PBB) is imposed on five sectors, namely the rural, urban, plantation, forestry and mining sectors. This research is a quantitative study using secondary data. The method used as an analytical tool in this study is by using Effectiveness Analysis and Growth Rate Analysis. The results of the study show. Regional Tax Effectiveness in West Aceh Regency which is less than 100% or close to 100% or variation between 92.39% and 119.79%, this indicates that the performance of the local government in conducting PBB-P2 collection is good, but still not optimal , because the realization of Land and Rural and Urban Building Taxes is more than the targeted target. Based on the tests that have been conducted, the results show that the level of realization and Effectiveness of Rural and Urban Land and Building Taxes on Regional Taxes fluctuated during the period 2010-2015Keywords: Land and Building Tax, Tax Effectiveness PBB, Growth rate PBB